Comparing Perceptual Visual Quality of Hybrid Neural and Ray Tracing in Foveated Rendering - Horácio Henriques; Alan de Oliveira; Eder Oliveira; Esteban Clua; Daniela Trevisan (Journal on Interactive Systems)
Enabling Foveated Rendering for VR devices displays is fundamental when dealing with real-time ray tracing. Combining traditional methods with Neural based strategies, such as NeRFs and 3D Gaussian Splatting, may impact on leveraging performance even more. In this work we enhance and validate how well our traditional Instant-NeRF reconstructs common ray-traced effects through user metrics and quality metrics. We also show that 3D Gaussian Splatting used in the periphery vision area presents better results than the perceptual quality achieved through NeRFs. We present a deep human perception experiment through different global illumination light effects.